Ethnic Cleansing of the Rohingyas: a Historical Analysis - Md. Abdus Samad (Paramita: Historical Studies Journal, 2023)
The ethnic Rohingyas have been living in the Rakhine State of Myanmar for centuries. Significant human rights problems persisted throughout the 2010s, including rape, sexual violence, politically motivated arrests, and an overall lack of the rule of law. Myanmar’s citizenship law of 1982 made the ethnic Rohingyas stateless. They were displaced from their homes by systematic violence. Government security forces were allegedly responsible for extrajudicial killings, arbitrary detentions, torture, mistreatment in detention, and systematic denial of due process of fair trials. The paper argues that the Rohingya genocide has been created in the Rakhine state with the ethnic cleansing of the Rohingyas since 2012. Ethnic cleansing of the Rohingyas has become a regional and international concern, not just an internal affair of Myanmar. This study attempts to explain the atrocity committed against the Rohingyas in terms of ethnic cleansing In the Rakhine State. The study is conducted based on multiple sources combining primary and closely related secondary materials, archival documents, newspapers, policy reports and pamphlets and leaflets published by different government and non-government agents and civil societies followed by the qualitative method. A balanced approach of data gathering and analysis will be used and maintained, including an analysis of both official and unofficial documents. Structured observations of the time to time will be very critically analyzed. The study finally suggests ways to improve Rohingya lives and secure regional peace.Etnis Rohingya telah tinggal di Negara Bagian Rakhine, Myanmar selama berabad-abad. Masalah hak asasi manusia yang signifikan masih terjadi sepanjang tahun 2010an, termasuk pemerkosaan, kekerasan seksual, penangkapan bermotif politik, dan lemahnya supremasi hukum. Undang-undang kewarganegaraan Myanmar tahun 1982 membuat etnis Rohingya tidak memiliki kewarganegaraan. Mereka terusir dari rumah mereka karena kekerasan sistematis. Pasukan keamanan pemerintah diduga bertanggung jawab atas pembunuhan di luar proses hukum, penahanan sewenang-wenang, penyiksaan, penganiayaan dalam penahanan, dan penolakan sistematis terhadap proses peradilan yang adil. Makalah ini berargumen bahwa genosida Rohingya terjadi di negara bagian Rakhine melalui pembersihan etnis Rohingya sejak tahun 2012. Pembersihan etnis Rohingya telah menjadi perhatian regional dan internasional, bukan hanya urusan internal Myanmar. Penelitian ini mencoba menjelaskan kekejaman yang dilakukan terhadap etnis Rohingya dalam kaitannya dengan pembersihan etnis di Negara Bagian Rakhine. Studi ini dilakukan berdasarkan berbagai sumber yang menggabungkan bahan-bahan primer dan sekunder, dokumen arsip, surat kabar, laporan kebijakan dan pamflet serta selebaran yang diterbitkan oleh berbagai lembaga pemerintah dan non-pemerintah serta masyarakat sipil yang diikuti dengan metode kualitatif. Pendekatan yang seimbang dalam pengumpulan dan analisis data akan digunakan dan dipertahankan, termasuk analisis terhadap dokumen resmi dan tidak resmi. Pengamatan terstruktur dari waktu ke waktu akan dianalisis dengan sangat kritis. Studi ini pada akhirnya menyarankan cara-cara untuk meningkatkan kehidupan Rohingya dan menjamin perdamaian regional.